POTENTIAL EXTRACT ANT NEST AS AN ANTHELMINTIC OF ASCARIS SUUM IN VITRO - Pemayun, Cok Krishna; Arjana, Anak Agung Gde; Dwinata, I Made (Buletin Veteriner Udayana, 2021)
Control of worm parasites can be done by administering worm medicine, one of them by using traditional medicine. One of them is an ant nest which has an anthelmintic potential in the A . suum worm. This study used A . suum worms obtained from Pesanggaran slaughterhouse, Denpasar and then grown in vitro. A total of 90 worms were divided into 6 treatment groups where each dose used 5 worms. Worm group P0 was soaked with 20ml Physiological NaCl as a negative control, P1 worm group soaked with 20ml Physiological NaCl and added 1% albendazole as positive control, P2 worm group soaked with 5% ant nest extract solution, P3 soaked group of worms with a solution of 10% ant nest extract, the P4 group of worms was soaked with a solution of 15% ant nest extract, P5 of the worm group was soaked with 20% ant nest extract solution. The results obtained showed that there was an increase in anthelmintic power of ant nest extract against A . suum worms. At the dose of 20% ant nest extract has the same anthelmintic power with positive control (93.33%). The ant nest extract is effective as an A . suum worm drug proven to have an anthelmintic effect so that its use can be developed to control ascariasis in pigs.